Case report: Cornelia de Lange Syndrome (CDLS) - Moretto, Marcelo Juliano [UNESP] (2012)
The Cornélia of Lange´s syndrome is a genetic anomaly, described and published by Cornelia Catharina of Lange in 1933, however, their aspects were described previously by Winfried Robert Clemens Brechmann in 1916, that’s why it is also known as Brachmann of Lange’s syndrome. The most frequent clinical characteristics include typical face dismorfia, variable degree of mental delay, anomalies of the hands and feet, multiple malformations, retardation of the pre and postnatal physical development and microcephaly variable intellectual compromising. Some facial characteristics are peculiar and they are mixed with the inherited lines of their own family, the united brows, the long lashes, the small nose, the round face, the fine lips and lightly inverted. As oral manifestations they present micrognathia, dental crowding, periodontal disease, delayed dental eruption, enamel hypoplasia, erosion of the enamel and dentine caused by stomach acids of the gastroesophageal reflux and atresia of the dental arches. The purpose of this paper is to present a clinical report of a boy bearer of this syndrome assisted at CAOE - FOA - UNESP, emphasizing the importance of multiprofessional team for the diagnosis and treatment of this syndrome.